Tracheal Extubation Under Deep Anesthesia Using Transnasal Humidified Rapid Insufflation Ventilatory Exchange vs. Awake Extubation: An Open-Labeled Randomized Controlled Trial - Qiu, Jin; Xie, Mian; Chen, Jie; Chen, Bing; Chen, Yuanjing; Zhu, Xiwen; Lin, Hui; Zhu, Tao; Duan, Guangyou; Huang, He (Frontiers in Medicine, 2022)
Background Tracheal extubation can be associated with several complications, including desaturation, agitation, hypertension, and tachycardia. We hypothesize that the use of transnasal humidified rapid insufflation ventilator exchange (THRIVE) immediately after extubation under deep anesthesia reduces the incidence of these adverse events. Methods One hundred patients who underwent elective abdominal surgery under general anesthesia were randomly assigned to undergo tracheal extubation under deep anesthesia employing THRIVE (THRIVE group) or awake extubation (CONTROL group). The primary outcome was the incidence of experiencing desaturation (SpO2 < 90%) at any time during emergence from anesthesia. Secondary outcomes included variations in heart rate and blood pressure, comfort level, bucking, and agitation. Results The THRIVE group showed a lower incidence of desaturation than the CONTROL group (12 vs. 54%, OR = 0.22 [95% CI, 0.10–0.49], P < 0.001). Less patients in the THRIVE group experienced a 20% (or more) increase in mean arterial pressure (4 vs. 26%, OR = 0.15 [95% CI, 0.04–0.65], P = 0.002). THRIVE patients did not suffer from agitation or bucking, while in the CONTROL group agitation and bucking occurred in 22 and 58% of the patients, respectively. Additionally, the THRIVE group showed a lower incidence of uncomfortable experience than the CONTROL group (8 vs. 36%, OR = 0.22 [95% CI, 0.08–0.61], P = 0.001). Conclusion Tracheal extubation under deep anesthesia using THRIVE decreases the incidence of desaturation and adverse haemodynamic events and increases patient satisfaction. Extubation under deep anesthesia using THRIVE might be an alternative strategy in selected patient populations.